1979
DOI: 10.1083/jcb.81.2.411
|View full text |Cite
|
Sign up to set email alerts
|

Membrane events involved in myoblast fusion.

Abstract: Myoblast fusion has been studied in cultures of chick embryonic muscle utilizing ultrastructural techniques. The multinucleated muscle cells (myotubes) are generated by the fusion of two plasma membranes from adjacent cells, apparently by forming a single bilayer that is particle-free in freeze-fracture replicas. This single bilayer subsequently collapses, and cytoplasmic continuity is established between the cells. The fusion between the two plasma membranes appears to take place primarily within particle-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
74
0
1

Year Published

1981
1981
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(84 citation statements)
references
References 29 publications
9
74
0
1
Order By: Relevance
“…Topologically, the process of myoblast fusion is not well understood but has been observed that transient vesicular structures appear at the sites of membrane fusion (6). Our data suggest that these vesicles may derive from the endocytic recycling compartment.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Topologically, the process of myoblast fusion is not well understood but has been observed that transient vesicular structures appear at the sites of membrane fusion (6). Our data suggest that these vesicles may derive from the endocytic recycling compartment.…”
Section: Discussionmentioning
confidence: 76%
“…In mammalian cells additional proteins that regulate myoblast fusion have been characterized, as well as many proteins implicated in myoblast differentiation (2)(3)(4). In both vertebrate and invertebrate systems, ultrastructural analysis of fusing myoblasts reveal the presence of vesicles accumulating at the sites of membrane fusion (5,6). Because vesicle fusion is a common feature of most cells, it is possible that aspects of the myoblast fusion machinery utilize pathways more commonly used by other cell types for intracellular trafficking.…”
mentioning
confidence: 99%
“…These prefusion myoblasts were distinguished from quiescent myoblasts by their elongated appearance and an accumulation of myoferlin-containing vesicles. The fusion of myoblasts to myotubes is known to involve vesicular structures (35). Similarly, the repair of torn surface membranes uses a number of mechanisms that may also include vesicular structures (36).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural studies have suggested that fusion is the result of the partial disappearance of the plasma membrane between two adjoining cells (63,75,118). An increase in membrane fluidity precedes myoblast fusion (51,104), and perturbations which are expected to alter fluidity, alter the recognition and fusion processes (68,131).…”
Section: Fusionmentioning
confidence: 99%